Digitalisasi UMKM dalam Pemasaran Peternakan Sapi di Tanjung Aur OKI - M. Syahrul; Jimmie Jimmie; Kemas Muhammad Wahyu Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to implement digitalization in the marketing process of Micro, Small, and Medium Enterprises (MSMEs) engaged in cattle farming in Tanjung Aur Village, Ogan Komering Ilir (OKI) Regency, through the development of a web-based cattle sales system. Digitalization is applied to overcome the limitations of traditional marketing, which requires buyers to visit the farm directly, resulting in limited market reach and inefficient transaction processes. The developed system provides features such as product information, online ordering, payment proof uploads, and data management for both administrators and farmers. The research adopts the Waterfall development model, consisting of requirement analysis, system design, implementation, and testing using the black box method. The results indicate that the implemented website successfully improves marketing effectiveness, expands customer reach, and simplifies the transaction process for both buyers and sellers. Furthermore, the system enhances time and cost efficiency compared to conventional manual methods previously used. With this digital platform, cattle-farming MSMEs in Tanjung Aur are expected to become more competitive and better prepared to adapt to the demands of the digital economy era.